Comparison of Fixed Assets Depreciation Method and Direction Influence on Company Profits in PT Akasha Wira International Tbk - Miftahul Anisa; Noor Amelia; Rina Pebriana (International Journal of Research in Vocational Studies (IJRVOCAS), 2021)
The purpose of this research is to determine the calculation of the depreciation cost allocation for fixed assets and its effect on operating income when using other alternative methods such as the double-declining balance depreciation method. Fixed assets will experience a decrease in economic value due to usage, damage, and obsolescence due to economic factors and technical factors. The method of depreciation of fixed assets that are used must be following the applicable accounting financial accounting standards, including the straight-line depreciation method and the double-declining balance depreciation method. Sources of data used in this study are secondary data types. Secondary data obtained in this study are from the official website of the IDX (Indonesia Stock Exchange) in the form of financial reports and fixed asset data for 2014-2018. The type of data of this research is quantitative, while the data processing method is the straight-line method and the multiple declining balance method. The results of the analysis in this study can be concluded that the method of depreciation of fixed assets used by the company is the straight-line depreciation method because operating income which is influenced by the straight-line depreciation method has a higher result compared to the double-decreasing balance depreciation method.